Concept for a study design in patients with severe community-acquired pneumonia: A randomised controlled trial with a novel IGM-enriched immunoglobulin preparation – The CIGMA study. Issue 6 (June 2015) - Welte, Tobias; Dellinger, R. Phillip; Ebelt, Henning; Ferrer, Miquel; Opal, Steven M.; Schliephake, Dorothee E.; Wartenberg-Demand, Andrea; Werdan, Karl; Löffler, Kurt; Torres, Antoni
Summary: Introduction: Severe community-acquired pneumonia is defined as community-acquired pneumonia that requires intensive medical care. Mortality in these patients is still high depending on time and admission. Since bad outcomes may occur despite antibiotic therapy to treat severe community-acquired pneumonia, the focus has shifted to targeting the host response. The CIGMA Study examines the safety and efficacy of the novel IgM-enriched immunoglobulin preparation BT086 when added to standard of care treatment. Methods/design: The aim of this multicentre, randomised, placebo-controlled, double-blind, parallel-group, adaptive group-sequential phase II study is to determine the efficacy and safety of BT086, an IgM-enriched immunoglobulin preparation, as an adjunctive treatment in mechanically-ventilated patients with severe community-acquired pneumonia. The increase of ventilator-free days is the primary endpoint in this study. For this trial, ventilator-free days are defined as the number of days between successful extubation from endotracheal ventilation and day 28 after enrolment of the patient into the study. Two interim analyses were considered for this study. Discussion: Several novel agents for treatment of sepsis have been evaluated in the last two decades; however, none has significantly reduced mortality rates. Failure was attributed to the heterogeneity of septic patients or sepsis. Severe community-acquired pneumonia was chosen as the indication for this study to increase homogeneity within this patient population. Trial registration: EUDRACT 2010-022380-35.